Впроваждення технологій data mining для моделювання економічних систем - Кирій, В. В.; Климко, Є. О. (My University, 2015)
Business intelligence is the set of techniques and tools (software) for the transformation of raw data into into useful knowledge for the purpose of making effective and informed management decisions. Data Mining is an analytic process designed to explore data (usually large amounts of data, also known as «big data»), to identify the interdependence and hypotheses . It is used in different spheres of life and took special place in management decisions
Keywords: data mining